El superhombre en los tiempo hipermodernos. Una aproximación al pensamiento de Friedrich Nietzsche y Gilles Lipovetsky - Murillo Lara, Salvador (Universidad Michoacana de San Nicolás de Hidalgo, 2012)
The purpose of this work is to meditate on the essential characteristics of the subjectivity modern and hypermodern and their relationship with the culture in which is inverse as well as the possibility or not in the creation of the conditions of different processes of subjectivity that you/they surpass the economic, political and social system that dominates at the present time, having as starting point those theoretical positions presented by the philosophers Friedrich Nietzsche and Gilles Lipovetsky. One theoretical approach among these two thinkers shows up with the purpose of explaining to us the form historical, cultural and social in the one that the contemporary men are configured with the one purpose of to have a better knowledge of us and to appreciate the different possibilities to create one construction different from human beings and of social and cultural institutions that facilitate one better realization. The Modernity, sustained in a capitalism that looks for the constant development of the forces productive, economic, it demanded, in a first moment, the formation of fellows governed by principles authoritarian, absolute, unquestionable. The modern fellows were characterized by an attitude of it conquers economic, politics and social, based on a firm faith in the future, in the science and in the technique; it was about an energetic subjectivity that looked for to break up with the sanguine hierarchies and of sovereignty sacred, by means of the ideas of the Reason, of the change and of the progress. The modern time formed a series of men and of women to those that it covered under a robe ideological-social certain; it conformed them under a certain subjectivity. The fellows, independently of the social classes to those that belonged, were characterized by their tendency of cult to the novelty and the change.

La finalidad de este trabajo es reflexionar sobre las características esenciales de la subjetividad moderna e hipermoderna y su relación con la cultura en la que se encuentra inmersa así como la posibilidad o no en la creación de las condiciones de procesos de subjetividad diferentes que ultrapasen el sistema económico, político y social que domina en la actualidad, teniendo como punto de partida los planteamientos teóricos presentados por los filósofos Friedrich Nietzsche y Gilles Lipovetsky. Una aproximación teórica entre estos dos pensadores se presenta con la finalidad de explicarnos la forma histórica, cultural y social en la que los hombres contemporáneos estamos configurados con el propósito de tener un mejor conocimiento de nosotros y apreciar las posibilidades distintas de crear una construcción diferente de seres humanos y de instituciones sociales y culturales que posibiliten una mejor realización. La Modernidad, sustentada en un capitalismo que busca el desarrollo constante de las fuerzas productivas, económicas, exigió, en un primer momento, la formación de sujetos regidos por principios autoritarios, absolutos, incuestionables. Los sujetos modernos se caracterizaron por una actitud de conquista económica, política y social, basada en una fe firme en el futuro, en la ciencia y en la técnica; se trató de una subjetividad enérgica que buscó romper con las jerarquías sanguíneas y de soberanía sagrada, mediante las ideas de la Razón, del cambio y del progreso. La época moderna formó una serie de hombres y de mujeres a los que cubrió bajo un ropaje ideológico-social determinado; los conformó bajo una subjetividad determinada. Los sujetos, independientemente de las clases sociales a las que pertenecían, se caracterizaron por su tendencia de culto a la novedad y al cambio.
Instituto de Investigaciones Filosóficas. Facultad de Filosofía. Programa Institucional de Maestría en Filosofía de la Cultura
Keywords: info:eu-repo/classification/cti/4; IIF-M-2012-0053; Científica; Friedrich Wilhelm Nietzsche; Hombre; Moderno; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/83